An approach of compartmentalisation in development of non-isothermal chemical reactor network models for the high speed simulation of iso-octane combustion - Khan, Zamier Ahmed (Centre for Bioprocess Engineering Research, 2015)
Every aspect of the modern day life relies on combustion, be it in motor vehicles, industrial equipment or power generation. The downside to the extensive use of combustion technology is the environmental pollution produced by the process. The lack of fast solving models to simulate combustion hampers the investigation into the optimisation of combustion processes. In this study, the compartment approach in developing a fast and accurate simulation is used to investigate combustion systems. A chemical reactor network (CRN) is proposed for the simulation of the combustion of iso-octane. The compartmentalisation of a combusting system involves proposing a reactor network based on the flow fields predicted by computational fluid dynamics (CFD). The first step in the development of such a model involves using of a reduced kinetic model representing thousands of combustion steps in a few elementary steps by lumping species. The reduced kinetic model used in this study consists of a five-step mechanism involving four pseudo species. The thermodynamic properties of the pseudo species in the system were regressed against experimental data and successfully validated using the plug flow and continuous stirred tank reactor sub-models. The reduced kinetic model was also further validated using Rapid Compression Machine data. The current study also modified the methodology for developing a CRN in order to make the CRN more predictive as compared to previous studies. This was achieved by incorporating non-isothermal sub-models into the network instead of isothermal sub-models that rely on the CFD temperature field. The network parameters were also correlated to the inlet Reynolds number in order to further increase the predictive nature of the network for industrial applications and to allow for the systems performance to be predicted over a wide range of input conditions. The investigation begins by conducting a CFD simulation of iso-octane combustion in a furnace and double inlet reactor assuming a one-step global reaction. On the basis of the CFD flow fields, a CRN was proposed and coupled to the reduced kinetics.